2021
DOI: 10.3892/wasj.2021.86
|View full text |Cite
|
Sign up to set email alerts
|

COVID‑19: An update of current knowledge (Review)

Abstract: There is a current public health issue threatening human health worldwide with the rapid spread of the novel coronavirus (2019-nCoV) or severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The infection was reported to first originate in bats and subsequently spread to humans via yet unknown source animals in Wuhan, Hubei, China in December, 2019. Coronavirus disease 2019 (COVID-19) caused by extreme acute respiratory coronavirus-2 syndrome (SARS-CoV-2) is an unprecedented healthy global emergency. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
4
0
2
Order By: Relevance
“…The HIF-1 (hypoxia-inducible factor-1α) signaling pathway, which plays an important role in virus infection and proinflammatory responses ( Tian et al, 2021 ; Serebrovska et al, 2020 ), was significantly enriched in gene expression profiles of Virofree treatment ( Figure 1B ), suggesting effects of the drug on this pathway to suppress IL-6 production, which is consistent with PCA loading scores ( Figure 1F ), and eventually inhibit the cytokine storm. GO enrichment indicated that Virofree can mediate clathrin-coated pit ( Alfarouk et al, 2021 ) and virus receptor activity, which are related to the virus–human entrance interaction ( Pandey et al, 2021 ). In contrast, the disease association via DO shows many COVID-19 symptoms or diseases in the upper range of Virofree treatment, including iron metabolism disorders, pulmonary arterial hypertension, idiopathic pulmonary hypertension, airway obstruction, and the common cold.…”
Section: Discussionmentioning
confidence: 99%
“…The HIF-1 (hypoxia-inducible factor-1α) signaling pathway, which plays an important role in virus infection and proinflammatory responses ( Tian et al, 2021 ; Serebrovska et al, 2020 ), was significantly enriched in gene expression profiles of Virofree treatment ( Figure 1B ), suggesting effects of the drug on this pathway to suppress IL-6 production, which is consistent with PCA loading scores ( Figure 1F ), and eventually inhibit the cytokine storm. GO enrichment indicated that Virofree can mediate clathrin-coated pit ( Alfarouk et al, 2021 ) and virus receptor activity, which are related to the virus–human entrance interaction ( Pandey et al, 2021 ). In contrast, the disease association via DO shows many COVID-19 symptoms or diseases in the upper range of Virofree treatment, including iron metabolism disorders, pulmonary arterial hypertension, idiopathic pulmonary hypertension, airway obstruction, and the common cold.…”
Section: Discussionmentioning
confidence: 99%
“…En cuanto a las características clínicas de la enfermedad, otro punto de contraste entre los odontólogos encuestados fue la dificultad de no encontrar sintomatología exclusiva que diferencie el contagio de COVID-19 en relación a otras patologías respiratorias. Aún así, al inicio de la pandemia se en-contró que gran cantidad de los pacientes presentaban anosmia, ageusia, mialgias y alteraciones gastrointestinales; lo que ayudó para una diferenciación más efectiva 14 . En este sentido, la gran mayoría de odontólogos concertó en que todos los síntomas respiratorios, deberían ser tomados como posibles sospechosos de COVID-19, hasta la confirmación de su diagnóstico.…”
Section: Conocimiento De Covid-19unclassified
“…The first group includes review articles. Such articles describe the basic virology of SARS-CoV-2, such as genomic characteristics and receptor use, highlighting its key difference from previously known coronaviruses (Boldyreva, 2020;Borges do Nascimento et al, 2021;Chams et al, 2020;Holmes et al, 2021;Hu et al, 2021;Pandey et al, 2021;Pathak, 2021;Sharma et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%